The Obama administration's nuclear weapon strategy : the promises of Prague - Warren, Aiden (Abingdon, Oxon : Routledge, 2014)
'This book comprehensively outlines and evaluates the key Obama nuclear weapons policies, developments and initiatives from 2008-2012. Beginning with the Administration's vision and goals posited in the 2009 Prague Speech and reaffirmed in the National Security Strategy of 2010, the book assess the Congressionally mandated Nuclear Posture Review (NPR), the New START Treaty, the pursuit of CTBT ratification, the Proliferation Security Initiative (PSI), the Fissile Material Cut-off Treaty (FMCT), the Non-Proliferation of Nuclear Weapons (NPT) Review the Conference, the Global Nuclear Security Summit and the extent to Obama in the context of such initiatives, has actually upheld the lofty goals posited in Prague and differentiated himself from the nuclear path pursued by the Bush Administration. Additionally, the book also evaluates the Obama Administration's dealings with other states in the context of its nuclear weapons policy - in particular, North Korea, Iran, Pakistan, India and China. Offering a comprehensive analysis of the current status of the US nuclear weapons strategy, this volume will be of great interest to scholars and students of American foreign policy, security studies and international relations'--
'This book will comprehensively outline and evaluate the key Obama nuclear weapons policies, developments and initiatives from 2008-2012'--
1. The vision of Prague -- 2. The Obama administration and the nuclear posture review -- 3. The Obama administration and the new START treaty -- 4. The Obama administration and the comprehensive nuclear-test-ban treaty -- 5. The Obama administration and other nuclear initiatives -- 6. The Obama administration and Iran, North Korea and Pakistan -- 7. The Obama administration and India, China and Israel.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Nuclear arms control -- Government policy -- United States -- History -- 21st century; Nuclear nonproliferation -- Government policy -- United States -- History -- 21st century